Bring on the Books for Everybody : How Literary Culture Became Popular Culture - Collins, Jim, 1953- (Book collections on Project MUSE., 2010)
Considers the proliferation of popular literary culture in the U.S.--from Oprah's book club to Miramax film adaptations to chick lit.